Inheritance in Contemporary America The Social Dimensions of Giving across Generations - Angel, Jacqueline L. (Johns Hopkins University Press, 2008)
With the baby boom generation on the cusp of retirement, life expectancies on the rise, and the nation's cultural makeup in flux, the United States is faced with social and policy quandaries that demand attention. How are elders to balance the competing claims of helping family members during their lifetime, saving for old age, and planning estates? What roles should the state, family, and individuals play in supporting people during later life? Are new familial gift-giving trends sustainable, and, if so, what effects might they have on future generations?Inheritance in Contemporary America tackles the complex legal, policy, and emotional issues that surround bequests and inheritances in an era of increasing longevity, broadening ethnicity, and unraveling social safety nets. Through empirical analyses, case studies, interviews, and anecdotes, Jacqueline L. Angel explains the historical nature of familial giving and how it is changing as the nation's demographics shift. She explores the legal, personal, and policy complexities involved in passing wealth down through generations and provides a cross-disciplinary context for exploring the indelible effects that newly unfolding inheritance practices will have on various societal cohorts and the nation in general.From nuclear and extended families to the state and nongovernmental bodies, Angel's engaging study explores how attitudes toward giving are evolving and confronts in stark terms the legacy that these shifts in attitude will leave. This book will be a vital tool for scholars and practitioners in gerontology, sociology, psychology, anthropology, economics, political science, and public policy.